PENGARUH PELATIHAN DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA DINAS PERDAGANGAN KABUPATEN BEKASI - Nunung Khodariyah; Muhamad Guruh (Journal of Research and Publication Innovation, 2025)
This study is to examine the influence of training and work discipline on employee performance at the Bekasi Regency Trade Service. This research method uses quantitative analysis, namely using in-depth data analysis in the form of numbers with a total of 83 respondents who are employees of the Bekasi Regency Trade Service. The sampling method used in this research is non-probability techniques. Data processing and analysis techniques use instrument testing, classical assumption testing, descriptive analysis, quantitative analysis and hypothesis testing. Based on research conducted, the effect of training on employee performance was obtained by the regression equation value Y = 7.626 + 0.620 X1. Hypothesis testing obtained a value of tcount > ttable or (13.651 > 1.663). Thus H0 is rejected and H1 is accepted. This shows that there is a partial influence of training on employee performance at the Bekasi Regency Trade Service. Meanwhile, Work Discipline on Employee Performance obtained a regression equation value of Y = 12.822 + 0.618 X2. The results of the hypothesis test obtained a value of tcount > ttable or (11.156 > 1.663). Thus, H0 is rejected and H2 is accepted, this shows that there is a partial influence of Work Discipline on Employee Performance at the Bekasi Regency Trade Service. Then the influence of Training and Work Discipline on Employee Performance Y = 6.233 + 0.424 X1+ 0.286 X2. The results of the hypothesis test obtained f count > f table (124.958 > 3.11). Thus, H0 is rejected and H3 is accepted, meaning that there is a simultaneous influence of Training and Work Discipline on Employee Performance at the Bekasi Regency Trade Service.